Multispecies and Stochastic issues : Comparative Evaluation of the Fisheries Policies in Denmark, Iceland and Norway - Agnarsson, Sveinn; Arnason, Ragnar; Johannsdottir, Karen; Ravn-Jonsen, Lars; K. Sandal, Leif; I. Steinshamn, Stein; Vestergaard, Niels (Copenhagen : Nordic Council of Ministers, 2008)
The aim of the project presented in this report has been to compare the fisheries polices in Denmark, Iceland and Norway with respect to economic performance and degree of sustainability. This has been done by comparing the actual stock and harvest development in the three countries to the optimal stock and harvest development suggested by a dynamic optimization model developed in the project. Thus we have defined indicators for stock and harvest performance. Emphasis in this project compared to earlier has been put on uncertainty and especially on multi-species interaction and modelling. The result of the project is that although there are clear signs of both harvest and stock overexploitation in all three countries, there were also significant differences. In particular, some of the results from the single-species model were turned around when species interaction was taken into account.